Entrepreneurship laboratory-based learning to increase students' interest in entrepreneurship - Sholekhah, Irmadatus; Indartono, Setyabudi; Fitriana, Erna (Jurnal Pendidikan dan Pengajaran, 2019)
The aim of this study was to determine the effect of entrepreneurship laboratories (UNY Plaza) on the students’ interest. The research was conducted at the Faculty of Economics, Universitas Negeri Yogyakarta. The questionnaire was used as a data collection tool distributed to 240 respondents. The results showed that the value of t count of 3.489 and t table of 1.6 means tcount > ttable. Then this study succeeded in proving the hypothesis which states that the UNY Plaza entrepreneurial laboratory has a positive effect on the interest of entrepreneurial students of the Faculty of Economics, University of Yogyakarta. Based on the analysis results, 29.6 percent of students' interest in entrepreneurship is explained by entrepreneurial laboratory variables, while 70.4 percent are explained by other factors that are not the focus of research.